Need to Know the Tribes of Tamil Nadu - S, Anandakumar (International Research Journal of Tamil, 2022)
Tribes are those who have seen the evolving changes from the ancient ways of life and have regulated their lives. Their social organization culture and culture is found according to the context in which they live. The so-called tribes are variously called in Tamil. Politicians refer to them as savages, literati, hill people, rain people, Tolkudi, Mudukudi, Adigudi, Purvagudi, and Gandhians refer to Gandhi as Kirijan. The tribe is an educated social group. These are people who can consistently live in a common place. Speakers of the common dialect are those who have a common one-sided social morality. Followers of common ancestral beliefs panchayat systems and religious belief systems. The Fifth Principle of Sangam Literature shows that it was the hill people who formed the way of life and culture of the ancient Tamil community according to their landscape. Thus, the majority of the indigenous people are indigenous peoples with traditional cultural identities.